PEMBEKALAN PELAYANAN BAGI CALON PELAYAN DAN PELAYAN DI GEREJA GBI GOSYEN BLESSING SURABAYA - Geovani, Loveilia; Hermanto, Yanto Paulus (Jurnal PKM Setiadharma, 2024)
The form of maturation of God's people is through service, and the Church needs God's servants to carry out Church service tasks. The younger generation needs to be involved because they need to be equipped and prepared for the continuity of the Church in the future. If they are not engaged, developed, and prepared for Christ, the world's ungodliness will attract them, and the Church has no future. Therefore, the aim of the Ecclesiastical Community Service in this research is to provide service provision for prospective ministers at GBI Gosyen Blessing. It is done so that those who have served do not fall into the wrong motivation for service and are competent in carrying out their Church service responsibilities. Those who have not yet served should start to be prepared and given an overview so that they will be stronger when serving. The qualitative research method uses data collection techniques such as observation, interview, literature study, and documentation. The implementation method is through seminars and simulations. The result of this activity was excellent because it practically increased the knowledge and skills that participants could put into practice directly. Church leaders also need to know the strategies for the movement of the Church in the future.